2007
DOI: 10.1177/1528083707078196
|View full text |Cite
|
Sign up to set email alerts
|

Thermogravimetric Analysis of a Cellulosic Fabric Incorporated with Ammonium Iron (II)-Sulfate Hexahydrate as a Flame-retardant

Abstract: The effect of ammonium iron (II)-sulfate hexahydrate [(NH 4 ) 2 Fe (SO 4 ) 2 Á6H 2 O] as a nondurable finish on the flammability of 100% cotton fabric, (woven construction, weighing 144 g/m 2 ) has been investigated. The laundered bone-dried, weighed fabrics are impregnated with suitable concentrations of the above-mentioned salt solution by means of squeeze rolls and drying at 110 C for 30 min. They are then cooled in a desiccator, re-weighed with an analytical balance, and kept under ordinary conditions befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In TGA analysis, it is widely reported that the primary thermal decomposition of cellulosic material occurs between 200 °C and 400 °C, while the initial decomposition takes place in the amorphous regions. [38][39] From the data shown in Figure 6, the main degradation step (T max corresponds to a huge weight loss) is found between 300 °C and 350 °C for bleached whole wood pulp, and from 250 °C to 300 °C for unbleached whole wood pulp. Also, the thermal stability of the bleached pulp is found to be very low (between 380 °C and 600 °C), compared to unbleached pulp.…”
Section: Resultsmentioning
confidence: 99%
“…In TGA analysis, it is widely reported that the primary thermal decomposition of cellulosic material occurs between 200 °C and 400 °C, while the initial decomposition takes place in the amorphous regions. [38][39] From the data shown in Figure 6, the main degradation step (T max corresponds to a huge weight loss) is found between 300 °C and 350 °C for bleached whole wood pulp, and from 250 °C to 300 °C for unbleached whole wood pulp. Also, the thermal stability of the bleached pulp is found to be very low (between 380 °C and 600 °C), compared to unbleached pulp.…”
Section: Resultsmentioning
confidence: 99%
“…The onset of decomposition was raised gradually from 250 C. After 300 C, the major decomposition started, and it reached the decomposition transition at 380 C. Although the exact temperature ranges of pyrolysis vary depending on the composition of cellulosic material and experimental conditions, it is carried out at three stages always [22,23].…”
Section: Resultsmentioning
confidence: 99%
“…A vertical flammability test method similar to the procedure described in DOC FF3-77 (U.S. Department of Commerce Standard) [22] was used. The full description of flammability testing has been demonstrated in previous investigations [23][24][25][26][27][28][29][30][31][32][33]. Briefly, specimens of size 220 mm × 80 mm were conditioned for 24 h at a relative humidity of 65 ± 2% and an average temperature which ranged between 20°C and 22°C prior to their evaluation.…”
Section: Flammability Testmentioning
confidence: 99%